EVALUATION OF FABRICATION ERRORS IN TITANIUM COMPOUNDS (American Journal of Technology and Applied Sciences, 2022)
The article covers the analysis of components of the cutting errors before choosing the type of control and presents a model of processing error based on analysis of reasons that cause deviation from linear dimensions during machining.